Influence of rare earths on the sintering of zirconia-yttria - Canova,I.C. (1999)
Yttria stabilized zirconia sintered by silicate glass phase with addition of ytterbium or gadolinium was investigated. The grain growth rate was found to be higher in the gadolinium doped samples. The glass phase of the ytterbium doped sample showed partial crystallization on cooling. Grain conductivity was found to be highest in samples with a half hour of sintering, having decreased due to stabilizing ion migration from the grains to the grain boundary glassy phase. The differences observed in the sintering behavior and properties of the sintered bodies are attributed to the different ionic radii of the Yb+3 and Gd+3 ions.